Development of React-Based E-Modules Using Local Riau Malay Wisdom in Learning Media Courses - Arien, Wilasari; Syafitra, Viony; Ramadhani, Masyitha; Fitrilinda, Dafetta (Universitas Pahlawan Tuanku Tambusai, 2025)
Technological developments with the industrial revolution 4.0 and society 5.0 have brought many changes to the world of education. Global demands require the world of education to always and always adapt technological developments to efforts to improve the quality of education, especially adapting its use to the world of education, especially in the learning process. Digital technology is useful for changing behavior in searching, collecting, documenting, processing and retransferring teaching materials according to needs. One of the teaching materials as a learning tool for students is a teaching module, which contains all systematic learning implementation plans starting from objectives, activities and assessments. Technology-based teaching modules or E-Modules aim to combine the use of information technology so that the modules can be more interesting and interactive. The Merdeka Curriculum does not only focus on the use of technology but also the implementation of local wisdom in the learning process. So that it can elevate regional diversity into a local advantage.The research will be conducted in May-October 2024 in the Community Education Study Program in learning media courses. This research is RD (Research and Development) research with the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. The development of this E-Module uses a REACT (Relating, Experiencing, Applaying, Cooperating, Transferring) based approach strategy, with the local wisdom of Riau Malay culture. The data collection instruments used were questionnaires and observation sheets. The data analysis technique that will be used is adjusted to the type of data collected, then analyzed descriptively and quantitatively.